"The Netflix effect" in Thailand: Industry and regulatory implications. (August 2021) - Ramasoota, Pirongrong; Kitikamdhorn, Abhibhu
Abstract: This study examines the economic, technological and cultural implications of Netflix in Thailand on local content industries and regulators. It also explores industry and regulatory responses to Netflix's emergence in a small market like Thailand. The study finds Netflix has markedly affected the industries' value chain but with contrasting impacts for broadcasting and film. Broadcasters have migrated online either by establishing their own platforms or by repositioning themselves as content providers for international streaming players in addition to acquiring business deals with other OTTs or broadcasters in regional markets. For film, a window of opportunity has been created by Netflix for small and independent filmmakers wishing to bypass the long-standing monopoly in the Thai film industry. Meanwhile, the country's regulator has looked for ways to bring foreign OTTs like Netflix under its oversight and may adopt a reward-based scheme while promoting local content industry with capacity-building and promotional measures. Highlights: Netflix has caused major Thai broadcasters to migrate online and to diversify as content providers to regional markets. Netflix has emerged as an important display alternative for filmmakers wishing to bypass monopoly in Thai film industry. Thai communication regulator looks into light-touch and reward-based approach to incorporate OTTs into its regulatory scheme.